On Cooperative Relay in Cognitive Radio Networks - Donglin Hu (EAI Endorsed Transactions on Mobile Communications and Applications, 2013)
Cognitive radios (CR) and cooperative communications represent new paradigms that both can effectively improve the spectrum efficiency of future wireless networks. In this paper, we investigate the problem of cooperative relay in CR networks for further enhanced network performance. We investigate how to effectively integrate these two advanced wireless communications technologies. In particular, we focus on the two representative cooperative relay strategies, decode-and-forward (DF) and amplify-and-forward (AF), and develop optimal spectrum sensing and p-Persistent CSMA for spectrum access.We develop an analysis for the comparison of these two relay strategies in the context of CR networks, and derive closed-form expressions for network-wide throughput achieved by DF, AF and direct link transmissions. Our analysis is validated by simulations. We find each of the strategies performs better in a certain parameter range; there is no case of dominance for the two strategies. The significant gaps between the cooperative relay results and the direct link results exemplify the diversity gain achieved by cooperative relays in CR networks.